The Construction of Religious Identity Among Islamic Education Students Amid the Current of Modern Islamic Thought - Nabilla Marsya Nada; Rafi Andika; Pitra Arya Oktama; Nurul Rahmad Ramadhan; Nurpitri Ikmalia; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
In today's era of globalization, shaping religious identity poses a significant challenge, particularly due to the influence of technology such as social media. Many students become negligent in performing religious practices as they get too absorbed in using social media. Additionally, the campus peer environment also plays a crucial role in shaping their character and habits, as peers can strongly influence changes in one’s attitude. Therefore, this study aims to understand how students of Islamic Religious Education (PAI) maintain a strong religious identity amid the currents of modern Islamic thought. This research employs a descriptive qualitative method and was conducted at UIN Raden Intan Lampung, involving second-semester PAI students as respondents. Data were collected through in-depth interviews using the snowball sampling technique and analyzed using the Miles & Huberman model. 1. Data Recuction 2. Data Presentation 3. Drawing Conclusions and Verivication. The findings indicate that PAI students’ religious identity has developed positively through campus learning processes, supportive peer environments, and the wise use of social media. These results demonstrate that PAI students are capable of firmly maintaining their religious identity despite the influences of globalization and contemporary Islamic thought. This research shows that Islamic Education students have a high enthusiasm for religious teachings, are motivated to learn, and are able to use technology well. They are also open to differences, establish good social relationships, and have awareness to learn independently.